The Dissidence of Reinaldo Arenas : Queering Literature, Politics, and the Activist Curriculum - Barros, Sandro R.; Willis, Angela L.; Ocasio, Rafael (Book collections on Project MUSE., 2022)
Through a multidisciplinary approach bridging educational, historiographic, and literary perspectives, The Dissidence of Reinaldo Arenas illuminates how Arenas's work remains a cutting-edge source of inspiration for today's audiences, particularly LGBTQI readers. It shows how Arenas's aesthetics contain powerful insights for exploring dissensus whether in the context of Cuba, broader Pan-American and Latinx-U.S. queer movements of social justice, or transnational citizenship politics. Carefully dissecting Arenas's themes against the backdrop of his political activity, this book presents the writer's poetry, novels, and plays as a curriculum of dissidence that provides models for socially engaged intellectual activism"--